Carbon footprint and energy analysis of bio‐CH4 from a mixture of food waste and dairy manure in Denver, Colorado. Issue 3 (26th September 2017) - Ankathi, Sharath K.; Potter, James S.; Shonnard, David R.
Abstract : Anaerobic digestion (AD) is a possible alternative to landfilling of food waste and conventional manure management in order to reduce methane emissions. We use the method of life cycle assessment in this study, and key results show that the AD Bio‐CH4 pathway has 15.5% lower greenhouse gas (GHG) emissions compared to the prior practice of composting of food waste and manure in Denver, CO. GHG emissions for Bio‐CH4 production from AD conversion of food waste and manure with avoiding of food waste landfilling and conventional management of dairy manure emits −3.5 kg CO2 equivalents/kg Bio‐CH4 assuming the electricity was generated using collected landfill gas. This emission intensity is favorably compared to that of fossil natural gas equal to 4.3 kg CO2 equivalents/kg CH4 equivalents. This method for carbon foot printing can be used to evaluate climate mitigation potential of other AD Bio‐CH4 projects. © 2017 American Institute of Chemical Engineers Environ Prog, 37: 1101–1111, 2018